Mirroring the Margins: Portrayal of Dalit identity in Limbale‟s The Outcaste - V G, Prasanth; S , Vineetha (International Journal of Psychosocial Rehabilitation, 2020)
Dalit literature emerged as a distinct genre in literature only during the post1960s with the awakening of Dalit consciousness. The Dalits in India were oppressed and brutally humiliated because of their belongingness to low castes. Denial of any kind of education and social acceptance kept their stories and experiences only in the oral form. Accessibility to education was the initial step for realizing the rotten politics of the caste system under which these people were exploited for centuries by the caste people. The emergence of Dalit writing helped them to express their suppressed feelings, gradually the marginal literature grabbed the attention of the literary world. In most of their narratives, reflections of their quest for identity can be seen. Dalit autobiographies are the vehicle for assertion of their identity. This paper attempts to analyse the Dalit consciousness in the text and it searches how a Dalit autobiography is different from other autobiographies. It attempts to trace out the challenges and struggles the narrator faced in his life for attaining an identity in the society.